Magnetic and resonance properties of multilayer (Gd/Si/Co/Si)ₙ films - Patrin, G.S.; Vas’kovskii, O.V.; Velikanov, D.A.; Svalov, A.V.; Volkov, N.V.; Eremin, E.V.; Panova, M.A. (Functional Materials, 2004)
Presented are the experimental investigation results of magnetic static and resonance properties of multilayer magnetic films in the system of 4f-3d elements separated by a semiconductor interlayer. Effects of temperature and magnetic field on interlayer coupling are detected. The role of the biquadratic exchange in formation of magnetic state in the whole system is established. Представлены результаты экспериментального исследования статических и резонансных магнитных свойств многослойных магнитных пленок в системе элементов 4f-3d, разделенных полупроводниковым промежуточным слоем. Обнаружено влияние температуры и магнитного поля на межслоевое взаимодействие. Установлена роль биквадратного обмена в формировании магнитного состояния системы как целого. Представлено результати експериментального досліджєння статичних та резонансних магнітних властивостей багатошарових магнітних плівок в системі елементів 4f-3d, розділених напівпровідниковим проміжним шаром. Виявлено вплив температури та магнітного поля на міжшарову взаємодію. Встановлено роль біквадратного обміну у формуванні магнітного стану системи як цілого.